2009
DOI: 10.1111/j.1472-4669.2008.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization by photosynthetic organisms: Evidence of coevolution of the organisms and their environment?

Abstract: Biomineralization is widespread among photosynthetic organisms in the ocean, in inland waters and on land. The most quantitatively important biogeochemical role of land plants today in biomineralization is silica deposition in vascular plants, especially grasses. Terrestrial plants also increase the rate of weathering, providing the soluble substrates for biomineralization on land and in water bodies, a role that has had global biogeochemical impacts since the Devonian. The dominant photosynthetic biomineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 122 publications
(276 reference statements)
1
40
0
Order By: Relevance
“…Dissolution of the externalised mineral skeleton in seawater undersaturated with respect to the mineral phase does not seem to be a major problem for acantharians (celestite) or diatoms (silica). At least for the diatoms, there is evidence that the organic layer surrounding the silicified frustules can decrease the dissolution rate of silica by 2 orders of magnitude (Natori et al 2006) so that the first-order rate constant for dissolution (d −1 ) falls from a value similar to the maximum specific growth rate (d −1 ) to a value of 0.01× the maximum specific growth rate (Raven & Giordano 2009, Raven 2011a. Milligan et al (2004) showed a small increase in the rate of dissolution of silica from diatom frustules with increasing CO 2 concentration in seawater; the mechanism of this effect is unknown.…”
Section: ω Cal and Dissolutionmentioning
confidence: 99%
“…Dissolution of the externalised mineral skeleton in seawater undersaturated with respect to the mineral phase does not seem to be a major problem for acantharians (celestite) or diatoms (silica). At least for the diatoms, there is evidence that the organic layer surrounding the silicified frustules can decrease the dissolution rate of silica by 2 orders of magnitude (Natori et al 2006) so that the first-order rate constant for dissolution (d −1 ) falls from a value similar to the maximum specific growth rate (d −1 ) to a value of 0.01× the maximum specific growth rate (Raven & Giordano 2009, Raven 2011a. Milligan et al (2004) showed a small increase in the rate of dissolution of silica from diatom frustules with increasing CO 2 concentration in seawater; the mechanism of this effect is unknown.…”
Section: ω Cal and Dissolutionmentioning
confidence: 99%
“…Such mineralization is seen among the bacteria (Heldal andTumyr 1983, Omelon et al 2006). A general review of biomineralization in photosynthetic organisms can be found in Raven and Giordano (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria induced mineralization occurred in both ancient and modern environments (Brady et al, 2009;Planavsky et al, 2009;Raven and Giordano, 2009); cyanobacteria-dominated carbonate formation occurred in oceans, lakes, springs, and soils during the Precambrian (Riding, 2000), whilst modern cyanobacteria-dominated carbonate formation occurs in highly alkaline aquatic environments (Thompson and Ferris, 1990;Braithwaite and Zedef, 1994;Dupraz et al, 2009;Power et al, 2009). Locations where modern cyanobacteria-dominated magnesium carbonate formation occurs include Lake Salda in Turkey, which is fed by ultramafic rock weathering products (e.g.…”
Section: Introductionmentioning
confidence: 99%